Is provisional stenting the effective option? The WIDEST study (Wiktor stent in de novo stenosis). Issue 5 (1st November 2000) - Fluck, D S; Chenu, P; Mills, P; Davies, A; Street, J; Paul, E; Balcon, R; Layton, C A
Abstract : AIM: To compare the immediate and late outcomes of patients treated by a policy of routine stent implantation with routine balloon angioplasty and the use of stents only when an ideal result has not been obtained. METHODS: A nine centre, multinational, randomised study of 300 patients with coronary artery disease thought suitable for treatment of a single lesion by balloon angioplasty or stent implantation. Only new lesions in patients who had not undergone previous bypass surgery were included, and totally occluded vessels were excluded. RESULTS: The initial procedure was considered successful in 96% of patients. There was more complete angiographic restoration of luminal diameter in patients treated by elective stent (minimum lumen diameter (MLD) 2.68 mm for stent v 2.27 mm for balloon; p < 0.007), but analysis of the subgroup of balloon angioplasty patients who crossed over to stenting showed that they achieved similar results to the elective stent group. Late luminal loss was greater in stented patients than in those undergoing balloon angioplasty only, and by six months the angiographic benefit of stenting had disappeared (MLD 1.90 mm for stent group v 2.00 mm for balloon angioplasty). Angiographic and clinical results in the balloon angioplasty group were assisted by the high crossover rate (30.1%). Both groups had similar symptom relief, with 58.9% of patients improving by two or more angina grades. The need for further revascularisation was also similar in the two groups at one year (18.2% in the stented group v 17.1% in the balloon angioplasty group). Haemorrhagic complications at the local arterial entry site were more common than expected and were distributed equally between the patients receiving full anticoagulation and those receiving antiplatelet treatment only. The results of both Wiktor stent placement and balloon angioplasty were similar to the findings in the stent group in previous randomised studies (Benestent II, STRESS). CONCLUSIONS: Provisional stenting appears to offer the same longer term outcome as elective stenting in this selected group of patients. Improvement in the results of conventional balloon angioplasty in the past 10 years means that a policy of obtaining an ideal result without the use of stents appears to be practicable in many of these patients, with consequent cost savings.